The impact geopolitical risk to firm value with political stability as moderation variable : evidence from ASEAN - Joseph, Widyatama; Kim, Sung Suk (Enrichment : Journal of Management, 2024)
International tensions are a concern for investors and companies because they can affect the results of investments made. This study examines the effect of geopolitical risk on firm value and political stability as a moderation in public companies in Indonesia, Malaysia, the Philippines, Vietnam, Thailand and Singapore. This study was conducted quantitatively on 3,477 companies from the period 2015-2022, unbalanced data with a total data sample of 22,572. The results of this study indicate that GPR is unable to significantly affect company value even though it has a negative coefficient. In addition political stability is also unable to moderate the effect of GPR on firm value